Novice teachers’ challenges and survival: where do Malaysian ESL teachers stand? - Senom, Fatiha; Zakaria, Abd Razak; Ahmad Shah, Shanina Sharatol (Science and Education Publishing, 2013)
The transition from the teacher education institution to life in a real classroom has been characterized as a type of reality shock in which beginning teachers realize that the ideals they formed while training may not be appropriate for the realism they are faced with during their first year of teaching [1]. Unfortunately, this concern is not fully addressed in schools in Malaysia as beginning teachers have the same responsibility as a teacher with many years of service. It is suggested that it is not until they have survived the initial shock of the first year that novices are able to begin to concentrate on the important areas of long-term planning, overall student goals, and individual students‟ needs [2]. This article examines challenges that novice teachers in Malaysia face in their early experience of teaching through a review of significant literature. Based on recent studies from the literature, these challenges are discussed and future direction for research in this field is suggested.